2015
DOI: 10.1590/0103-6440201300055
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Surgical Bone Defects Grafted with Hydroxylapatite + β-TCP and Irradiated with λ=850 nm LED Light

Abstract: The treatment of bone loss due to different etiologic factors is difficult and many techniques aim to improve the repair, including a wide range of biomaterials and recently, photobioengineering. This work aimed to assess by histological analysis the repair of bone defects grafted with biphasic synthetic micro-granular HA + β-TCP associated with LED phototherapy. Forty rats were divided into 4 groups (Clot, LED, Biomaterial and LED + Biomaterial) each subdivided into 2 subgroups according to the time of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…A study by Soares et al [65] utilized λ 850 nm LED PBM irradiation on bone defects grafted with HA and βTCP showed to be effective in positively modulating the process of bone repair in rat's femur bone defect submitted or not to biomaterial irradiation. Hence, this study has poorly reported the laser parameters in terms of energy, power density and treatment duration [65]. Another study by Soares et al showed the influence of the LED (λ 78nm) and laser (λ 850 ± 10 nm) PBM on surgical bone defects repair whether augmented with or without biphasic synthetic micro-granular HA + βTCP.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Soares et al [65] utilized λ 850 nm LED PBM irradiation on bone defects grafted with HA and βTCP showed to be effective in positively modulating the process of bone repair in rat's femur bone defect submitted or not to biomaterial irradiation. Hence, this study has poorly reported the laser parameters in terms of energy, power density and treatment duration [65]. Another study by Soares et al showed the influence of the LED (λ 78nm) and laser (λ 850 ± 10 nm) PBM on surgical bone defects repair whether augmented with or without biphasic synthetic micro-granular HA + βTCP.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight the laser light used for laser phototherapy (LPT). Over the past 20 years, experimental protocols have been proposed for a considerable number of procedures involving bone repair in animals and humans [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These protocols are now also used as an aid to an efficient repair of mineralized tissues, as LPT accelerates bone repair by directly affecting, in different ways, the new bone formation.…”
Section: Laser In Dentistrymentioning
confidence: 99%
“…Fibroblast proliferation and its increased activity have been previously detected in individuals and cultures of irradiated cells and are responsible for the high concentration of collagen fibers observed in the irradiated bone. Our previous studies indicate that the effective result of LPT is observed when the treatment is performed in the initial stages of repair, when a large cell proliferation occurs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Vascular responses to LPT have also been suggested as one of the possible mechanisms responsible for the positive clinical results observed.…”
Section: Laser In Dentistrymentioning
confidence: 99%
See 2 more Smart Citations